Functional dependency and cardiometabolic multimorbidity in older people: pooled analysis of individual-level data from 20 countries - Bai, Anying; Chen, Qiushi; Geldsetzer, Pascal; Gray, Muir; Xie, Zhilan; Zhang, Daqian; Bärnighausen, Till; Hu, Yixin; Jiang, Yu; Chen, Simiao (Age & ageing, 2024)
The impact of cardiometabolic multimorbidity (CMM) on functional dependency (FD) is well established, but the temporal effect of FD on CMM and its mechanisms remain underexplored.A multicohort study pooled data from three international cohorts.Data were sourced from the Health and Retirement Study (USA), the China Health and Retirement Longitudinal Study (China) and the Survey of Health, Ageing and Retirement in 18 European countries.FD was defined as the inability to perform basic activities of daily living (ADLs) and instrumental ADLs (IADLs) independently. CMM was defined as the co-occurrence of two or three cardiometabolic diseases, including diabetes, heart disease and stroke. Generalised estimating equation models assessed associations between FD and CMM, with mediation analysis using the Karlson, Holm and Breen method to explore the effects of hypertension and depressive symptoms. Sensitivity analyses ensured robustness.The final cohort included 157 512 and 190 249 individuals for ADL and IADL analyses, respectively. CMM prevalence was 18.97% and 16.65% in these groups. FD was consistently associated with higher CMM risk, with odds ratios ranging from 1.47 (95% confidence interval: 1.33-1.63) to 1.56 (1.42-1.73). Hypertension and depressive symptoms increased CMM risk, particularly at higher FD levels. Mediation analysis showed hypertension and depressive symptoms accounted for 8.01%-16.43% and 12.04%-18.36% of the adverse effect of FD on CMM, respectively, with more pronounced effects among smokers and heavy drinkers.Targeted interventions focusing on hypertension, mental wellness, lifestyle factors, and integrated treatments for FD are crucial to prevent CMM in older adults.